PENGARUH RELEVANCE, PERCEIVE USEFULNESS, PERCEIVE EASE OF USE PADA SIKAP TERHADAP PENGGUNAAN LAYANAN SISTEM INFORMASI E-DISHUB SURABAYA - Dini Fatmawati; Santirianingrum Soebandhi; Agus Baktiono (Universitas Trunojoyo Madura, 2017)
This study aimed to analyze the effect of relevance, perceive usefulness and perceive ease of use on attitudes towards using information system services provided by e-Dishub Surabaya, especially on KIR test information content at PKB Tandes UPTD region. This study used quantitative method with a questionnaire for data collection. Sample in this study was the people who were doing KIR testat UPTD PKB Tandeswith total of 100 respondents. Data were analyzed using multiple linear regression analysis. Results showed that all hypotheses proposed were supported. Means that relevance, perceive usefulness, perceive ease of use have significant effect, partially and simultaneously, on attitude towards using e-Dishub application.